Time and Thing: Einstein’s Influence on Zubiri’s Thought Concerning Linear Time - Durán Allimant, Ronald; Espinoza Lolas, Ricardo; Landaeta Mardones, Patricio; Orellana Estay, Óscar (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This essay seeks to explain Xavier Zubiri’s concept of linear time in his work Espacio.Tiempo. Materia. In his concept of time, we can see the profound influence of Albert Einstein’s Theory of Restricted Relativity. In order to comprehend more fully, then, what time means in the light of things, we have to study briefly how Zubiri himself understands Einstein concerning this theme.
Keywords: Zubiri; Einstein; time; relativity; respectivity